CIAT in Asia 40 years on - International Center for Tropical Agriculture (2017)
“In Vietnam, we cannot talk about CIAT without mentioning the cassava story. This is one of the most successful stories of international cooperation. Until the recent years, in the 1990s, this crop was neglected with a few thousand hectares, and had almost no significant economic value. Farmers grew for their local need. Thanks to the continuing effort from scientists of CIAT in cooperation with breeders and farmers in Vietnam, productivity of cassava has doubled over the last years. Cassava has become third important export crop after rice and coffee, providing jobs and income to millions of farmers, and bringing to the country annually more than USD1 billion.